Prison Leave in Romania and the Power of Street Level Bureaucrats - Durnescu, Ioan (European journal on criminal policy and research, 2020)
The paper analyses the policy and legal framework around prison leave in Romania. Prison leave practice is also analysed based on interviews with prison staff. The paper explores the historical evolution of prison leave in Romania, covering both the use of leave as a reward and the application of discretion in awarding leave. In the first part, we will provide contextual information about prisons and prison regime in Romania. In the second part of the paper, we will introduce the rules and regulations relating to prison leave and will comment on these. The conclusion of this analysis is that the decision-making process continues to allow too much discretion in relation to prison leave, and this may create problems for procedural justice and legitimacy. Prison guards—those called to trigger the rewards procedure—enjoy vast amounts of unguided power, and the appeal mechanisms are sometimes informal or inaccessible for prisoners. The article calls for in-depth empirical research on this topic and puts forward a few recommendations intended to improve the policy regarding prison leave in Romania. The article further discusses a number of improvements which would make the practice of awarding prison leave more predictable and equitable for prisoners.